Poster No. 108 Effectiveness and safety of P2Y12 inhibitor pretreatment for primary PCI in STEMI: Systematic review and meta-analysis. (21st October 2022) - Presume, João; Gomes, Daniel; Ferreira, Jorge; Albuquerque, Francisco; Almeida, Manuel Sousa; Uva, Miguel Sousa; Aguiar, Carlos; Mendes, Miguel
Abstract: Double antiplatelet therapy (DAPT) with both aspirin and P2Y12 inhibitors in patients with STEMI has been shown to be associated with better clinical outcomes. Yet, there is uncertainty regarding the optimal timing for its initiation. This study is a systematic review and meta-analysis of the current evidence on pretreatment with P2Y12 inhibitors in patients with STEMI submitted to primary percutaneous coronary intervention (PCI). We performed a systematic search of electronic databases Pubmed, CENTRAL and Scopus until April/22. Studies were considered eligible if they were comparing P2Y12 inhibitor upstream administration vs. downstream use in patients with STEMI submitted to PCI. Studies with patients treated with fibrinolysis or medical therapy only were excluded. Outcomes were assessed at the shortest follow-up available. Out of 2336 articles, 18 studies were included (3 RCT and 17 non-RCT), with a total of 79300 patients (52439 in the pretreatment arm). Pretreatment was associated with a reduction in definite stent thrombosis (OR 0.59 [0.37–0.94]), all-cause death (OR 0.77 [0.60–0.97]) and cardiogenic shock (OR 0.60 [0.48–0.75]). It was also associated with lower incidence of TIMI flow < 3 pre-PCI (OR 0.78 [0.67–0.92]). However, it was not associated with a significant reduction in recurrent MI (OR 0.93 [0.57–1.52]). Regarding safety outcomes, pretreatment was not associated with higher risk of major bleeding events (OR 0.83 [0.75–0.92]). Pretreatment with DAPT, including a P2Y12 inhibitor, was associated with better pre-PCI coronary perfusion, lower risk for definite stent thrombosis, cardiogenic shock, and all-cause mortality. No sign of potential harm from this approach was encountered.